The PBL materials integrated with critical thinking skills in improving EFL learners’ reading comprehension and linguistic awareness - Ketut Anom Pujayanti; Haerazi Haerazi; Arif Rahman (Universitas Muhammadiyah Malang, 2026)
This study investigates the effectiveness of problem-based learning (PBL) materials integrated with critical thinking skills in enhancing English as a Foreign Language (EFL) learners’ reading comprehension and linguistic awareness. Employing a mixed-method concurrent embedded design, the research involved 75 senior high school students in Central Lombok, Indonesia, divided into experimental and control groups. The experimental group received PBL-based instruction, while the control group was taught using non PBL instruction. Quantitative data were collected through pre- and post-tests on reading comprehension and linguistic awareness, complemented by a critical thinking assessment. Qualitative data were obtained from learner interviews to capture perceptions and experiences. The results revealed that the experimental group demonstrated significant improvements in both reading comprehension and linguistic awareness compared to the control group. Statistical analyses, including t-tests and ANOVA, confirmed the positive impact of integrating PBL with critical thinking, with reading comprehension showing greater gains than linguistic awareness. Qualitative findings further highlighted that students valued the collaborative, problem-solving nature of PBL, which fostered deeper engagement with texts and encouraged reflection. However, while improvements in critical thinking were evident, they were relatively modest, suggesting the need for explicit scaffolding of higher-order reasoning within the PBL framework. The findings confirm that PBL integrated with critical thinking constitutes an effective instructional model for promoting EFL learners’ linguistic and cognitive development, offering valuable implications for teachers, curriculum designers, and policymakers seeking to foster meaningful, student-centered language learning.